Small is beautiful: what flies tell us about ERM protein function in development. - Polesello, C.; Payre, F. (Trends in Cell Biology, 2004)
Actin dynamics is recognized as being a determinant in many developmental processes and pathologies, such as cell polarity, morphogenesis and tumour metastasis. However, how actin interacts with the plasma membrane is poorly understood. Although numerous studies in cell culture point to the crucial role of Ezrin, Radixin and Moesin (ERM) proteins in the actin-membrane link, genetic approaches in mice have not yet revealed their activity during development. Drosophila has recently become an alternative and promising system for the genetic study of ERM protein function. This article focuses on advances made in flies, providing evidence for the evolutionary conservation of functional properties of ERM proteins, in addition to shedding new light on their importance for development.